Karyotype Analysis of Two Epiphytic Ferns From Bangladesh - Azad, Abul Kalam; Zaman, Shahriar; Mazid, Md Abdul; Kabir, Golam (Journal of Life and Earth Science, 2014)
DOI: http://dx.doi.org/10.3329/jles.v7i0.20128 J. Life Earth Sci., Vol. 7: 99-104, 2012